High sensitivity C-reactive protein in pre-hypertensive young adults - Ab Rahman, Jamalludin; Mohd Shah, Azarisman Shah; Mohd Shah, Aida Nur Sharini; Abdullah, Nor Zamzila; Abdullah, Aszrin (Elsevier Ltd, 2019)
High sensitivity C-reactive protein (hs-CRP) levels have been recommended by the Center for Disease Control and Prevention (CDC) and the American Heart Association (AHA) to be part of the global risk prediction assessment for cardiovascular diseases (CVD) in asymptomatic individuals. Hypertension is one of the major risk factors of CVD. It is usually preceded by a pre-hypertensive state in which, without intervention may lead to hypertension at an accelerated rate. Since studies have reported variation in the hs-CRP levels amongst different ethnic groups, it is therefore crucial to study the hs-CRP values in our population for it to be more a more reliable parameter when used as an early predictor of CVD. This study was conducted to compare the hs-CRP levels between the normotensive and pre-hypertensive categories of blood pressure (BP) among young adults in Kuantan, Pahang, Malaysia. Methods: A total of 167 young adults were recruited in this comparative cross sectional study, 96 (57.5%) in the normotensive (NT) and 7 1 (42.5%) pre-hypertensive (PHT) groups. Blood samples were assayed for hs-CRP levels. There was significant difference in the levels of the hs-CRP (p- 0.031) between the NT and PHT groups. The geometric mean of hs-CRP at 95% CI for NT was 0.87mg/L (0.79 to 0.96) and PHT, 1.42 mg/L (0.95 to 2.12), respectively. In our study, the hs-CRP levels in the PHT subjects were significantly higher compared to the NT group.